Evolution and Conservative Christianity: How Philosophy of Science Pedagogy Can Begin the Conversation - James, Christine (Spontaneous Generations: A Journal for the History and Philosophy of Science, 2008)
I teach Philosophy of Science at a four-year state university located in the southeastern United States with a strong college of education. This means that the Philosophy of Science class I teach attracts large numbers of students who will later become science teachers in Georgia junior high and high schools—the same schools that recently began including evolution "warning" stickers in science textbooks. I am also a faculty member in a department combining Religious Studies and Philosophy. This means Philosophy of Science is often expected to provide dialogue, debate, and bridge-building on the issues of creationism and evolution. I am expected to provide a welcoming atmosphere to all the religious perspectives that the students bring to class, but at the same time I feel responsible for giving them a serious respect for evolution. This tension between religious tolerance and secular science education has had important consequences in American schools, most notably with the issue of Intelligent Design Theory (ID) in the classroom.
James, Christine (2008). Evolution and Conservative Christianity: How Philosophy of Science Pedagogy Can Begin the Conversation. Spontaneous Generations: A Journal for the History and Philosophy of Science. 1 electronic record (PDF).
Keywords: Human Evolution, Philosophy, Philosophy of Science, Education, Pedagogy